Vitamin D metabolism in dogs with and without hypercalciuric calcium oxalate urolithiasis. (9th March 2019) - Groth, Elizabeth M.; Lulich, Jody P.; Chew, Dennis J.; Parker, Valerie J.; Furrow, Eva
Abstract : Background: There are abnormalities in vitamin D metabolism in people with calcium nephrolithiasis, but limited data are available on vitamin D status in dogs with calcium oxalate (CaOx) urolithiasis. Objective: To compare serum concentrations of vitamin D metabolites in dogs with and without hypercalciuric CaOx urolithiasis. Animals: Thirty‐eight dogs with (n = 19) and without (n = 19) a history of CaOx urolithiasis and hypercalciuria. Methods: Retrospective cross‐sectional study. Serum 25‐hydroxyvitamin D [25(OH)D], 1, 25‐dihydroxyvitamin D [1, 25(OH)2 D], and 24, 25‐dihydroxyvitamin D [24, 25(OH)2 D] were measured. The ratios of 25(OH)D/24, 25(OH)2 D and 1, 25(OH)2 D/25(OH)D were compared between cases and controls. Results: There were no significant differences between cases and controls when comparing 25(OH)D, 24, 25(OH)2 D, 1, 25(OH)2 D, or 1, 25(OH)2 D/25(OH)D. Cases had higher 25(OH)D/24, 25(OH)2 D (median = 1.40, range = 0.98‐1.58) compared to controls (median = 1.16, range = 0.92‐2.75; P  = .01). There was overlap in the ranges for 25(OH)D/24, 25(OH)2 D between cases and controls, but 6 cases (32%) had ratios above the control dog range. There was a moderate positive correlation between the ratio of 25(OH)D/24, 25(OH)2 D and urinary calcium‐to‐creatinine ratios ( r  = 0.40, 95% confidence interval = 0.10‐0.64; P  = .01). Conclusions and Clinical Importance: These data suggest that decreased conversion of 25(OH)D to 24, 25(OH)2 D occurs in a subset of dogs with CaOx urolithiasis. Abnormalities in vitamin D metabolism might contribute to stone risk in dogs.